The Friend Zone - Jimenez, Abby (New York : Forever, 2019)
"Kristen Peterson doesn't do drama, will fight to the death for her friends, and has no room in her life for guys who just don't get her. She's also keeping a big secret: facing a medically necessary procedure that will make it impossible for her to have children. Planning her best friend's wedding is bittersweet for Kristen--especially when she meets the best man, Josh Copeland ... Even her dog, Stuntman Mike, adores him. The only catch: Josh wants a big family someday"--Back cover.
Keywords: Man-woman relationships -- Fiction; Weddings -- Fiction. -- Planning; Infertility -- Fiction; Childlessness -- Fiction; Romance fiction